Forage and grain yields and forage composition of barley, wheat, and oats - Oltjen, J.; Bolsen, K.; Moore, W. (Kansas State University. Agricultural Experiment Station, 2011)
We harvested barley, wheat and oat varieties at the dough stage. Average yields in tons of 65% moisture forage/acre were 9.3 (barley), 10.2 (hard wheat), 9.5 (soft wheat), and 10.0 (oats). Barley variety yields varied most because of winter kill. Barley forages were the most digestible; oats, the least digestible. Crude fiber and grain contents of the forages were highly correlated with digestibility. Barley yielded highest in digestible dry matter, but hard wheat yields were more consistent from year to year.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Forage yields; Grain yields; Barley; Wheat; Oats